In Vitro Test of Antibacterial Ethanol Extract, n-Hexane Fraction and Ethyl acetate Fraction of Sungkai Leaf (Peronema cenescens) Against Salmonella typhi - Br., Sitepu Nadroh (Asian Journal of Pharmaceutical Research and Development, 2020)
Object: This study aims to look at the class of compounds and the comparison of the antibacterial activity of ethanol extract, n-hexane fraction and ethyl acetate of Sungkai leaves against Salmonella typhi. Methods: Study included phytochemical screening and in vitro antibacterial testing of ethanol extract, n-hexane fraction and ethyl acetate of Sungkai leaves against Salmonella typhi. Results: obtained groups of chemical compounds alkaloids, flavonoids, glycosides, anthraquinones, tannins and triterpenoids/steroids on Sungkai leaf powder. Ethanol extract of Sungkai leaves obtained resistance at a concentration of 20% by 12.7 mm, and inhibition of the ethyl acetate fraction at a concentration of 20% of 14.8 mm. Conclusion: Ethyl acetate fraction of Sungkai leaves have antibacterial properties against S. typhi which is greater than ethanol extract and hexane fraction of leaf heal.